Measuring stakeholders’ attitudes toward sustainable development of conference and congress tourism: Serbia case study - Ivkov, Milan; Milošević, Srđan; Dimić, Nemanja; Đoković, Filip (Hotel and Tourism Management, 2024)
Purpose – Scientific publications regarding business tourism, especially those which incorporate elements of sustainable development, still remain scarce in the existing literature. Therefore, the aim of this paper is to examine attitudes of local tourist organizations, travel agencies, catering establishments, chambers of commerce and other relevant stakeholders towards the sustainable development of conference and congress tourism (CCT) in Vojvodina, Serbia. Methodology – In order to investigate the attitudes of stakeholders (n=174), the adapted sustainable tourism attitude scale (SUS-TAS) was used in this paper. Moreover, the responses of the directors (managers) of local tourism organizations to several open-ended questions, which make an integral part of the survey, are also presented. Findings – The research instrument proved to be reliable. Based on other applied analyses (t-test and ANOVA), the existence of numerous statistically significant differences in the responses in relation to gender, job position, sector of work, age and education were identified. Implications – Apart from theoretical contribution, this paper reveals what aspects of CCT are in stakeholders’ main focus and what seems to be out of their radar. This should help defining necessary actions for further improvements of CCT. Lastly, study limitations and future research guidelines are discussed.